2016
DOI: 10.1016/j.nicl.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Impaired dynamic cerebrovascular response to hypercapnia predicts development of white matter hyperintensities

Abstract: PurposeTo evaluate the relationship between both dynamic and steady-state measures of cerebrovascular reactivity (CVR) and the progression of age-related white matter disease.MethodsBlood oxygen level-dependent (BOLD) MRI CVR scans were acquired from forty-five subjects (age range: 50–90 years, 25 males) with moderate to severe white matter disease, at baseline and one-year follow-up. To calculate the dynamic (τ) and steady-state (ssCVR) components of the BOLD signal response, the PETCO2 signal waveform was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 35 publications
6
50
0
Order By: Relevance
“…The current study demonstrates that WM CVR information is informative and robust: namely, conventional CVR and VTF‐AUC in WM were lower in WMH groups compared with healthy participants, and VTF‐TTP was lower in healthy participants, compared with the moderate WMH group in WM. These results support previous studies in people with WMH, which report that CBF and CVR are reduced in WMH vulnerable regions . Collectively, these findings suggest that CVR impairment in WM occurs due to potentially both timing and amplitude deficits, which aligns with the pathophysiology that shows smaller arteries and/or arterioles are subject to functionally impaired vasodilation in CSVD, whereas GM is less affected .…”
Section: Discussionsupporting
confidence: 90%
“…The current study demonstrates that WM CVR information is informative and robust: namely, conventional CVR and VTF‐AUC in WM were lower in WMH groups compared with healthy participants, and VTF‐TTP was lower in healthy participants, compared with the moderate WMH group in WM. These results support previous studies in people with WMH, which report that CBF and CVR are reduced in WMH vulnerable regions . Collectively, these findings suggest that CVR impairment in WM occurs due to potentially both timing and amplitude deficits, which aligns with the pathophysiology that shows smaller arteries and/or arterioles are subject to functionally impaired vasodilation in CSVD, whereas GM is less affected .…”
Section: Discussionsupporting
confidence: 90%
“…Prior studies showed impaired white matter CVR is associated with disruption of white matter at the microstructural scale in participants with WMH (Sam, Conklin, Holmes, et al, 2016;Sam, Peltenburg, Conklin, et al, 2016). Prior studies showed impaired white matter CVR is associated with disruption of white matter at the microstructural scale in participants with WMH (Sam, Conklin, Holmes, et al, 2016;Sam, Peltenburg, Conklin, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Impaired cerebrovascular autoregulation may also be contributing to chronic ischemia (Mikulis, 2013). Exhaustion of cerebrovascular reserve and the associated chronic ischemic injury to gray matter and white matter is hypothesized as the cause of disruption of both the network nodes and edges of the connectome respectively (Sam, Conklin, Holmes, et al, 2016;Sam, Peltenburg, Conklin, et al, 2016). Exhaustion of cerebrovascular reserve and the associated chronic ischemic injury to gray matter and white matter is hypothesized as the cause of disruption of both the network nodes and edges of the connectome respectively (Sam, Conklin, Holmes, et al, 2016;Sam, Peltenburg, Conklin, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations